CLAIMING THE SHIELDS: LAW, ANTHROPOLOGY, AND THE ROLE OF STORYTELLING IN A NAGPRA REPATRIATION CASE STUDY (Utah Environmental Law Review; Vol 29 No 1 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}   After some odd twists and turns by the end of the twentieth century the shields were in the possession of Capitol Reef National Park. At that point, three claims were filed for repatriation of the shields under the auspices of the Native American Graves Protection and Repatriation Act (NAGPRA or the Act). In this paper, I use the controversy surrounding the repatriation of the three shields as the basis for examining the question of who owns the past. In particular, I examine how the repatriation process under NAGPRA addresses that question. I do this through the methodology of a case study. Because of the fact-intensive inquiry required under NAGPRA, and because NAGPRA repatriation cases are not typically resolved through court litigation, a case study seems an appropriate way to proceed with this examination.